Low Blue Light Enhances Phototropism by Releasing Cryptochrome1-Mediated Inhibition of PIF4 Expression . Issue 4 (17th June 2020) - Boccaccini, Alessandra; Legris, Martina; Krahmer, Johanna; Allenbach-Petrolati, Laure; Goyal, Anupama; Galvan-Ampudia, Carlos; Vernoux, Teva; Karayekov, Elizabeth; Casal, Jorge J.; Fankhauser, Christian
Abstract : Persistent low blue light in natural canopy shade relieves the inhibitory effect of cryptochrome1 on PHYTOCHROME INTERACTING FACTOR4, enhancing phototropism in de-etiolated Arabidopsis seedlings. Abstract: Shade-avoiding plants, including Arabidopsis ( Arabidopsis thaliana ), display a number of growth responses, such as elongation of stem-like structures and repositioning of leaves, elicited by shade cues, including a reduction in the blue and red portions of the solar spectrum and a low-red to far-red ratio. Shade also promotes phototropism of de-etiolated seedlings through repression of phytochrome B, presumably to enhance capture of unfiltered sunlight. Here we show that both low blue light and a low-red to far-red light ratio are required to rapidly enhance phototropism in Arabidopsis seedlings. However, prolonged low blue light treatments are sufficient to promote phototropism through reduced cryptochrome1 (cry1) activation. The enhanced phototropic response of cry1 mutants in the lab and in response to natural canopies depends on PHYTOCHROME INTERACTING FACTORs ( PIFs ). In favorable light conditions, cry1 limits the expression of PIF4, while in low blue light, PIF4 expression increases, which contributes to phototropic enhancement. The analysis of quantitative DII-Venus, an auxin signaling reporter, indicates that low blue light leads to enhanced auxin signaling in the hypocotyl and, upon phototropic stimulation, a steeper auxin signaling gradient across the hypocotyl. We conclude that phototropic enhancement by canopy shade results from the combined activities of phytochrome B and cry1 that converge on PIF regulation.